2014
DOI: 10.5897/ijbc2014.0685
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of small mammals In Borena-Sayint National Park, South Wollo, Ethiopia: Implications of habitat specialization

Abstract: The study on distribution and diversity of small mammals in Borena-Sayint National Park (BSNP), South Wollo Zone, Ethiopia was conducted from December, 2009 to April, 2010. Representative sample sites were taken from each habitat type and surveyed using random line transect method. Five species of rodents and two species of shrews were identified and recorded from BSNP. Small and large sized Sherman and snaps traps were used to trap small mammals and morphometric measurement was taken for the species. From a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…During the present study, we recorded the presence of two Ethiopian endemic rodents—Awash Multimammate Mouse Mastomys awashensis (Lavrenchenko et al, 1998) and Ethiopian White‐footed Mouse Stenocephalemys albipes (Rüppell, 1842; Figure 1) in KSNP. The morphometric and cranio‐dental measurements (Table 1) are well within the range of the species (Mengistu et al, 2015; Meseret & Solomon, 2014) and the skull morphology (Figure 2) also confirms for better identification. We captured a total of 17 individuals comprise different age groups of Mastomys awashensis and 55 individuals of Stenocephalemys albipes from all habitat types except the grass land.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…During the present study, we recorded the presence of two Ethiopian endemic rodents—Awash Multimammate Mouse Mastomys awashensis (Lavrenchenko et al, 1998) and Ethiopian White‐footed Mouse Stenocephalemys albipes (Rüppell, 1842; Figure 1) in KSNP. The morphometric and cranio‐dental measurements (Table 1) are well within the range of the species (Mengistu et al, 2015; Meseret & Solomon, 2014) and the skull morphology (Figure 2) also confirms for better identification. We captured a total of 17 individuals comprise different age groups of Mastomys awashensis and 55 individuals of Stenocephalemys albipes from all habitat types except the grass land.…”
Section: Resultssupporting
confidence: 66%
“…During the present study, we recorded the presence of two Ethiopian endemic rodents-Awash Multimammate Mouse Mastomys awashensis (Lavrenchenko et al, 1998) and Ethiopian White-footed Mouse Stenocephalemys albipes (Rüppell, 1842; Figure 1) in KSNP. The morphometric and cranio-dental measurements (Table 1) are well within the range of the species (Mengistu et al, 2015;Meseret & Solomon, 2014) and the skull morphology (Figure 2…”
Section: Re Sultssupporting
confidence: 58%
“…It lies in the woredas of Borena to the south, Saynt to the north and Mehal Saynt to the east. e largest portion of the park is found in Borena woreda [13].…”
Section: Description Of the Study Area Borena Saynt Nationalmentioning
confidence: 99%
“…e park is heterogeneous in vegetation type and classified into two vegetation zones, which occur below and above 3000 meters [14]. Out of the total 30 mammalian species recorded in the park, Ethiopian wolf (Canis simensis), Gelada baboon ( eropithecus gelada), Stark`s hare (Lepus strackii), and Menelik's bushbuck (Tragelaphus scriptus meneliki) are endemic [11,13].…”
Section: Description Of the Study Area Borena Saynt Nationalmentioning
confidence: 99%
“…Similar results were recorded in different parts of the country by using similar line transect techniques. For instance, Girma et al [ 16 ] recorded 18 species of medium and large mammalian species in Kaka and Hunkolo Fragnents, Meseret and Solomon [ 33 ] recorded 23 medium and large mammalian species from Borena-Sayint Park, south of Wollo, Ethiopia, and Kasso et al [ 34 ] and Gebo et al [ 35 ] identified 21 species in the Chilalo-Glama Forest Priority Area and Faragosa-Fura Landscape, Gamo Zone, Ethiopia, respectively. On the contrary, Lemma and Tekalign [ 25 ] documented only a total of eight medium and large mammalian species in the Humbo Community-Based Forest Area, Southern Ethiopia, which is smaller than that of the present study.…”
Section: Discussionmentioning
confidence: 99%